An analysis of streaming performance in 3G mobile network / Samsiah Ahmad - Ahmad, Samsiah (Faculty of Information Technology and Quantitative Science, 2005)
The third generation, 3G, mobile telephone systems are new technologies that have been used developed country such as United State, Australia and Japan. It is designed for multimedia communication and will offer us similar services as in our stationary computers. Streaming is one of the services that provided in 3G networks and it is a common technology for video transmission over the Internet and with 30 it is supposed to become popular also in our mobiles. However how good the streaming performance using in 30 mobile networks still questionable. The aim of this study is to analyze streaming performance in 30 mobile networks. For this research we used two types service that provided in 30 mobile there are Video-On demand and live streaming. In order to deliver both streaming media in 30 mobile some specification need to be considered including the type of media that being used. Therefore for this research we compared two types of media that can be used in 30 mobile phone. There are MPEO-4 and RealVideo media streams which both media type can be compared using parameters; stream availability, startup time, thinning and Loss and rebuffering or interruptions. These parameters are being used during the testing to collect data which then to be analyzed. Data that has been analyzed will be use by developer as guidance to enhance streaming performance in 30 mobile networks.